Using Synthetic ApoC-II Peptides and nAngptl4 Fragments to Measure Lipoprotein Lipase Activity in Radiometric and Fluorescent Assays - Oldham, Dean; Wang, Hong; Mullen, Juliet; Lietzke, Emma; Sprenger, Kayla; Reigan, Philip; Eckel, Robert H.; Bruce, Kimberley D. (Frontiers in Cardiovascular Medicine, 2022)
Lipoprotein lipase (LPL) plays a crucial role in preventing dyslipidemia by hydrolyzing triglycerides (TGs) in packaged lipoproteins. Since hypertriglyceridemia (HTG) is a major risk factor for cardiovascular disease (CVD), the leading cause of death worldwide, methods that accurately quantify the hydrolytic activity of LPL in clinical and pre-clinical samples are much needed. To date, the methods used to determine LPL activity vary considerably in their approach, in the LPL substrates used, and in the source of LPL activators and inhibitors used to quantify LPL-specific activity, rather than other lipases, e.g., hepatic lipase (HL) or endothelial lipase (EL) activity. Here, we describe methods recently optimized in our laboratory, using a synthetic ApoC-II peptide to activate LPL, and an n-terminal Angiopoietin-Like 4 fragment (nAngptl4) to inhibit LPL, presenting a cost-effective and reproducible method to measure LPL activity in human post-heparin plasma (PHP) and in LPL-enriched heparin released (HR) fractions from LPL secreting cells. We also describe a modified version of the triolein-based assay using human serum as a source of endogenous activators and inhibitors and to determine the relative abundance of circulating factors that regulate LPL activity. Finally, we describe how an ApoC-II peptide and nAngptl4 can be applied to high-throughput measurements of LPL activity using the EnzChek™ fluorescent TG analog substrate with PHP, bovine LPL, and HR LPL enriched fractions. In summary, this manuscript assesses the current methods of measuring LPL activity and makes new recommendations for measuring LPL-mediated hydrolysis in pre-clinical and clinical samples.